The Success of English Language Training at Time Language Centre in Padang City - Apriani, Joti; Aini, Wirdatul (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2026)
This study aims to determine the success factors of English language training at Time Language Centre. This research used a qualitative method with a case study approach. This research was conducted at Time Language Centre, located at Jl. Limau Bali No. 9J Lapai, Padang, West Sumatra. Data were collected through interviews, observation, and documentation. Data analysis was conducted through the processes of data collection, data reduction, data presentation, and drawing conclusions. The data sources in this study were obtained from research subjects and informants, where the research subject was the researcher herself and the informants were the management, instructors, and training participants. The results indicate that the success of English language training at Time Language Centre is influenced by the careful management of five main factors: training participants, instructor competence, education and training facilities, curriculum, and education and training funds. The synergy between these factors indicates that training success is not determined by a single factor, but rather by the comprehensive management of all education and training components.